CULTURAL LANDSCAPE: GENERAL IDEAS AND CONCEPTS, RESEARCH APPROACHES (Scientific journal of the Fergana State University, 2024)
This article analyzes the concept of “cultural landscape” and ideas associated with its organization, and also examines the theoretical and practical aspects of approaches to the study of cultural landscapes. The importance of protected natural areas in the formation of cultural landscapes is also analyzed.